Geographical variation in the chemical composition, anti-inflammatory activity of the essential oil, micromorphology and histochemistry of Schinus terebinthifolia Raddi. (30th January 2023) - Marangoni, Janaine Alberto; da Costa Pinto, Jannaina Velasques; Kassuya, Candida Aparecida Leite; de Oliveira Junior, Pedro Cruz; dos Santos, Sidney Mariano; Cardoso, Claudia Andrea Lima; Silva, Rosilda Mara Mussury Franco; Espíndola da Silva, Marcia; Machado, Camila Dias; Manfron, Jane; Formagio, Anelise Samara Nazari
Abstract: Ethnopharmacological relevance: Schinus terebinthifolia Raddi (Anacardiaceae) is rich in essential oil, distinguished by a predominance of monoterpenes and sesquiterpenes, it being widely used in traditional medicine for the treatment of inflammations. Aim of study: This study's objective was to investigate the chemical composition of the essential oil of S. terebinthifolia (EOST) collected in six states of Brazil, evaluate its anti-inflammatory effects in mice, and analyze the histochemistry and micromorphology of leaves and stems. Materials and methods: Aerial parts of S. terebinthifolia were collected in six states of Brazil, and the essential oil was extracted by hydrodistillation and analyzed by gas chromatography-mass spectrometry (GC–MS). The histochemistry and micromorphology of leaves and stems were performed using standard reagents, light and field emission scanning electron microscopy, beyond energy-dispersive X-ray spectroscopy. The EOST were evaluated for anti-inflammatory activity and hyperalgesia using the carrageenan-induced paw edema methodology. Results: The EOST showed variation across the six states in its yield (0.40%–0.86%) and chemical composition: hydrocarbon monoterpenes (28.76%–47.73%), sesquiterpenes, (31.43%–41.76%), oxygenated monoterpenes (14.31%–19.57%), and oxygenated sesquiterpenes (4.87%–14.38%). Both α-pinene and limonene were predominant constituents of essential in five regions, except for one state where α-phellandrene and limonene were the dominant components. A comprehensive description of the leaf and stem micromorphology and histochemistry was performed. In the in vivo testing, all EOST samples exerted antiedematogenic and anti-hyperalgesic effects, when tested in a carrageenan-induced paw inflammation (mechanical and thermal hyperalgesia) model with oral doses of 30 mg/kg. Conclusion: Our results indicate that the EOST samples collected in six Brazilian states differed in their chemical composition but not their anti-inflammatory and antihyperalgesic effects, which was correlated with the synergistic effect of its components, collaborating the etnhopharmacologycal use of this plant due to its an anti-inflammatory effect. Also, micromorphology and histochemistry of leaves and stems presented in this study provide anatomical and microchemical information, which aids species identification. Graphical abstract: Image 1 Highlights: Essential oil demonstrated variation in yield and chemical composition. The α-pinene and limonene were predominant constituents of five regions. A comprehensive description of the leaf and stem micromorphology and histochemistry was performed. S. terebinthifolia leaves collected in six states of Brazil produce an analgesic and/or anti-inflammatory activity.